2023
DOI: 10.33503/journey.v6i1.2498
|View full text |Cite
|
Sign up to set email alerts
|

The Perspectives of EFL Students on the Technological Pedagogical Content Knowledge (TPACK) of Their Teachers

Abstract: The objective of this current research was examining EFL students' point of views on their teachers' TPACK (technological pedagogical content knowledge). A growing body of research had been conducted to investigate instructors' TPACK. However, few research have addressed the evaluation of TPACK from the perspective of EFL students. The students’ view offers a relatively objective perspective of instructors' TPACK to provide valuable feedback for further evaluation on their classroom practice. A survey method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…However, they considered their teachers to be relatively less proficient in the three other components: TCK, TPK, and TPCK. In addition, the result of this research is similar with Ningtyas et al, (2023), they found that tertiary EFL students believed their teachers were competent in overall components of TPACK. Then, it was discovered that EFL students thought their teachers had a good level in four components: CK, TK, PK, and TPCK.…”
Section: Discussionsupporting
confidence: 81%
“…However, they considered their teachers to be relatively less proficient in the three other components: TCK, TPK, and TPCK. In addition, the result of this research is similar with Ningtyas et al, (2023), they found that tertiary EFL students believed their teachers were competent in overall components of TPACK. Then, it was discovered that EFL students thought their teachers had a good level in four components: CK, TK, PK, and TPCK.…”
Section: Discussionsupporting
confidence: 81%